The efficacy of local household detergents against Escherichia Coli - Noor Alshurdin, Siti Hajar; Abdul Raman, Ali Imran; Mohamed, Danial Azrayyhaqim; Zomorni, Fatin Nursyahidah; Zaidi, Noorakmal; Zulkepli, Norhelena Aleesa; Abd Malik, Nur Izzah Aishah; Abdullah, Wan Amir (2024)
With the increasing concern about bacteria spreading to the surroundings from clothes that were not washed properly, understanding the effectiveness of antibacterial properties in detergents becomes imperative. Thus, this study was conducted to assess the antibacterial efficacy of selected detergents against Escherichia coli (E. coli) through standard microbiological techniques. Two different commercial household detergents were prepared with different concentrations of 25%, 50%, and 100% to compare their effectiveness. E. coli was cultured and isolated for macroscopic and microscopic identification. The antibacterial activity of selected detergents against E. coli was assessed through disk diffusion method, conducted in triplicates for 24 hours. Other variables included 90% alcohol as the positive control and distilled water as the negative control. The findings indicate that all tested detergents with different concentration exhibited some degree of antibacterial activity, there were significant variations in their effectiveness against E. coli. Detergent A demonstrated strong bactericidal properties, significantly reducing bacterial growth compared to detergent B, and the most effective concentration of detergent is 100% for both. The results highlight the importance of evaluating the antibacterial effectiveness of household detergents to ensure optimal domestic hygiene and prevent the spread of potentially harmful bacteria like E. coli.